2018
DOI: 10.1021/acssuschemeng.8b04700
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Distribution Effect on Cassava Starch and Cassava Bagasse Biocomposites

Abstract: Regarding the growing interest in the development of biodegradable films from renewable sources, this work is focused on the utilization of cassava roots bagasse as a natural filler of cassava starch films. Homogenous films could be obtained by casting molding from gelatinized cassava starch suspensions, plasticized with glycerol and containing 1.5% w/w bagasse. In order to study the particle size effect on films properties, three different fibrous residue fractions (particles sized between 500–250, 250–53, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 40 publications
(91 reference statements)
0
12
0
1
Order By: Relevance
“…This effect could be attributed how filler particles with different sizes fit within the matrix, probably giving place to more clustered and therefore steady structures. [46,47] It is well known that particle size, dispersion state, and interfacial interaction are three crucial parameters for the development on performance of filler/polymer biocomposites. [48] Codou et al [49] found that the smaller particles were beneficial in reducing the porosity of the biocarbon-reinforced nylon 6/polypropylene biocomposites.…”
Section: Discussionmentioning
confidence: 99%
“…This effect could be attributed how filler particles with different sizes fit within the matrix, probably giving place to more clustered and therefore steady structures. [46,47] It is well known that particle size, dispersion state, and interfacial interaction are three crucial parameters for the development on performance of filler/polymer biocomposites. [48] Codou et al [49] found that the smaller particles were beneficial in reducing the porosity of the biocarbon-reinforced nylon 6/polypropylene biocomposites.…”
Section: Discussionmentioning
confidence: 99%
“…It was then ground in a knife and ball mill, and separated in different granulometry, by means of an electromagnetic sieve shaker for 20 min, using different sieve diameters. In this study, only fibers with a size of about 0.08 to 0.07 mm (170 to 200 mesh sieve) were used (Brito et al., 2019; Versino & García, 2019). The BSG was comprehensively characterized elsewhere (cellulose, hemicellulose, lignin, and total dietary fibers contents: 28, 32, 26, and 14 wt.%, respectively) (Mendes et al., 2020b).…”
Section: Methodsmentioning
confidence: 99%
“…Treatments with MA, NaOH, and PCL‐g‐MA increased the adhesion between the PCL and treated shells (black circles), promoting greater PCL wettability in the shell and reducing the shell particles pulled from the matrix 44,45 …”
Section: Resultsmentioning
confidence: 99%